Calculation of Fuel Economy at Expense of Blade Turbine Improvement - I. N. Spagar (Наука и техника)
The paper analyses dependence of fuel economy on geometrical and gas dynamic characteristics of turbine blades, namely: coefficient of cascade energy loss, blade height, relative blade spacing, inand out-cascade angles.